How Does Transformational Leadership Affects Work Engagement? A Systematic Literature Review - Jimmy S Hadi; Ani Ratnasari; Stefanus Sadana (PT Mattawang Mediatama Solution, 2023)
Transformational leadership and work engagement are two important factors that contribute to organizational management effectiveness. However, the picture of the two's connection remains hazy. This is the first study to examine the findings of empirical research conducted from 2017 to July 2023 in order to better understand the influence and relationship between transformational leadership and work engagement. This review selected 27 papers that matched the qualifying requirements and gave an analysis of each of the 27 papers' findings. The outcomes of this review show that TFL has a considerable effect on WE. TFL influences employees in general through the process of internalizing values. Internalization serves as a job resource for WE. Internalization of these values can take the form of increasing inspirational appeal, creating a work environment that allows employees to learn from mistakes, inviting them to work above and beyond minimum standards so that employees can demonstrate their full potential, and other practical steps that form a positive mindset in employees. This research also confirms another finding, namely that TFL and WE are connected. This review underlines that the two variables' interaction is interconnected, interdependent, and mutually reinforcing.